An update on rib grafting in rhinoplasty: which rib is right?. Issue 4 (5th August 2022) - Drake, Virginia E.; Mowery, Alia J.; Nellis, Jason C.
Abstract : Purpose of review: In revision or posttraumatic rhinoplasty, the quantity and quality of septal cartilage available for grafting is often deficient and auricular cartilage often provides insufficient strength for structural nasal reconstruction. Accordingly, rib cartilage serves as a reliable, abundant source of cartilage for grafting. However, the various sources of rib cartilage carry respective benefits and weaknesses. This review examines recent studies, novel applications and a comparison of the primary sources of rib cartilage, including autologous cartilage, irradiated cadaveric rib and fresh frozen cadaveric cartilage. Recent findings: Options for rib cartilage include autologous, irradiated cadaveric rib, and more recently, reports on fresh frozen cadaveric cartilage. Studies continue to conclude that autologous and irradiated donor cartilage carry equivalent results, have similar rates of complication and have a comparable cost profile. Summary: Regardless of the source, rib cartilage plays an important role in structural rhinoplasty, especially in revision cases. Although the risks, benefits and long-term results of autologous and radiated homologous cartilage have been evaluated in observational studies, fresh frozen rib cartilage will need further follow up before widespread use, although preliminary literature shows promise.